Ceramic Composites from Bovine Hydroxyapatite, ZrO2@SiO2, and Hydroxyapatite + 15%ZrO2@SiO2. (2022) - Azevedo-Silva, L.J.; Padovini, D.S.S.; Ferrairo, B.M; Minim, P.R.; Pereira, L.F.; Monteiro, R.S.; Fortulan, C.A.; Lisboa-Filho, P.N.; Borges, A.F.S.
Abstract : Purpose/Aim: This study aimed to synthetize and evaluate the biaxial flexural strength of dense polycrystalline experimental composites from bovine hydroxyapatite (HA); ZrO2 @SiO2 coreshell; and HA + 15%ZrO2 @SiO2 . Materials and Methods: HA was extracted from solid bovine bone residues and broken to submicrometric powder. ZrO2 coreshell covered by SiO2 was synthetized through Stober sol-gel method. Disc-shaped specimens (12 ×1.2 mm) were synthesized at 1300 C (HA), 1340 C (ZrO2 @SiO2 ), and 1300 C (HA + 15%ZrO2 @SiO2 ). The sintering temperatures followed the maximum temperature indicated for each material, according to the literature. Next, the specimens were submitted to biaxial flexural strength test. The results were analyzed regarding normality by Shapiro Wilk test. Comparisons were made by Kruskall-Wallis test (α = 0.05) followed by Tukey test. Results: DRX analysis demonstrated the characteristic peaks of ZrO2 and HA in HA +15%ZrO2 @SiO2 . It was also possible to observe HA crystallinity decreasing with the addition of the coreshell. ZrO2 @SiO2 biaxial flexural strength (140.2 16.05 MPa) was significantly greater (p<.001) than HA (99.2 8.66 MPa), and HA + 15%ZrO2 @SiO2 (107.5 5.44 MPa). HA and HA + 15%ZrO2 @SiO2 showed no statistically differences. Conclusions: ZrO2 @SiO2 sintering was a promising alternative to make crystalline materials and HA-ZrO2 @SiO2 composite can be a promising biomaterial, after the search for adjustments in the sintering process.